2012
DOI: 10.1016/j.ajhg.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Mutation of CCDC78 in a Unique Congenital Myopathy with Prominent Internal Nuclei and Atypical Cores

Abstract: Congenital myopathies are clinically and genetically heterogeneous diseases that typically present in childhood with hypotonia and weakness and are most commonly defined by changes observed in muscle biopsy. Approximately 40% of congenital myopathies are currently genetically unresolved. We identified a family with dominantly inherited congenital myopathy characterized by distal weakness and biopsy changes that included core-like areas and increased internalized nuclei. To identify the causative genetic abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 19 publications
2
52
1
1
Order By: Relevance
“…All embryos were manually dechorionated at day 1 after fertilization. Histopathology, including immunofluorescence analysis of isolated myofibers and EM of muscle from whole embryos, was performed as previously described (25,26). this was performed by Complete Genomics and processed through their Standard Pipeline v. 2.2.…”
Section: Lmod3 Mo Zebrafishmentioning
confidence: 99%
“…All embryos were manually dechorionated at day 1 after fertilization. Histopathology, including immunofluorescence analysis of isolated myofibers and EM of muscle from whole embryos, was performed as previously described (25,26). this was performed by Complete Genomics and processed through their Standard Pipeline v. 2.2.…”
Section: Lmod3 Mo Zebrafishmentioning
confidence: 99%
“…Our group (Dowling) recently identified a dominant splice site mutation in CCDC78 in a family with an unusual congenital myopathy associated with moderate muscle weakness, exercise intolerance, and a combination of cores, protein aggregates, and central nuclei on muscle biopsy [110]. Using a morpholino-based approach, we showed that zebrafish that model the splice site alteration seen in patients exhibit abnormal triad structure and accumulate RyR1 and DHPR aggregates throughout their myofibers.…”
Section: Ccdc78-associated Myopathymentioning
confidence: 99%
“…CNM is due to X-linked recessive mutations in MTM1 encoding myotubularin ["X-linked myotubular myopathy (XLMTM)"] [47], autosomal-dominant mutations in DNM2 encoding dynamin2 [48] and the BIN1 gene encoding amphiphysin 2 [49], autosomal-recessive mutations in BIN1 [50], RYR1 [14], and TTN encoding titin [51], and rarer backgrounds [52][53][54]. Whilst mutations in MTM1 and BIN1 are typically associated with a "pure" CNM picture, histopathological appearance in particular in DNM2-, RYR1-and TTN-related forms is more variable and may also feature cores, CFTD and dystrophic features [14,55,56].…”
Section: Myotubular/centronuclear Myopathy (Mtm/cnm)mentioning
confidence: 99%